Oral Health Access and Early Caries in Childhood in a Primary Care Service in Southern Brazil: A Cross-Sectional Study - Lucas Eduardo Jardim; Mayara Rodrigues Pereira; Márcia Cançado Figueiredo; Daniel Demétrio Faustino-Silva (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the prevalence of early childhood caries and its association with Child's Programmatic Action dental visits in a Primary Care Service. Material and Methods: A cross-sectional analytical study was carried out at the Health Centers of the  Grupo HospitalarConceição  Community Health Service in Porto Alegre, RS, Brazil. Mothers answered a questionnaire containing socioeconomic data, eating habits and oral care of their children. Caries examination was performed by two examiners calibrated using WHO criteria. Results: Eighty-one children with mean age of 58.8 (SD=4.8) months were evaluated, 58% were male. Caries prevalence was 43%, with mean dmft = 1.7 and mean dmfs = 3.09. In the multivariate analysis, there was a statistically significant association of caries with maternal schooling (PR=1.31, 95%CI=1.06-1.62, p=0.012), family income (PR=0.93, 95% CI=0.90-0.97, p<0.001), adequacy of the number of childcare visits (PR=0.68, 95%CI=0.54-0.86, p=0.001) and number of visits to the dentist (PR=1.04, 95%CI=1.01-1.06, p=0.001). Conclusion: Ensuring access to childcare and early dental consultation, while the family context is disregarded, does not seem to be enough to reduce caries. It is necessary to think of non-conventional oral health promotion strategies in Primary Health Care taking into account the territory and social determinants since changes to eating and oral hygiene habits and behaviors are still a challenge to the control of childhood caries.